Question Number 80139 by M±th+et£s last updated on 31/Jan/20 | ||
![]() | ||
Commented by M±th+et£s last updated on 31/Jan/20 | ||
![]() | ||
$$\left[{Q}\mathrm{80131}\:{Reposted}\right] \\ $$ | ||
Commented by mr W last updated on 31/Jan/20 | ||
![]() | ||
$${if}\:{something}\:{is}\:\infty,\:{you}\:{may}\:{not} \\ $$$${treat}\:{it}\:{as}\:{a}\:``{normal}''{value},\:{otherwise} \\ $$$${we}\:{would}\:{get}\:{things}\:{like} \\ $$$$\mathrm{1}×\infty=\infty \\ $$$$\mathrm{2}×\infty=\infty \\ $$$$\Rightarrow\mathrm{1}×\infty=\mathrm{2}×\infty \\ $$$$\Rightarrow\frac{\mathrm{1}×\infty}{\infty}=\frac{\mathrm{2}×\infty}{\infty} \\ $$$$\Rightarrow\mathrm{1}=\mathrm{2} \\ $$ | ||
Commented by MJS last updated on 31/Jan/20 | ||
![]() | ||
$$\mathrm{try}\:\mathrm{this}: \\ $$$$\left(\mathrm{e}^{\frac{\mathrm{1}}{\mathrm{e}}} \right)^{\left(\mathrm{e}^{\frac{\mathrm{1}}{\mathrm{e}}} \right)^{\left(\mathrm{e}^{\frac{\mathrm{1}}{\mathrm{e}}} \right)^{...} } } =? \\ $$ | ||
Commented by M±th+et£s last updated on 31/Jan/20 | ||
![]() | ||
$$−{j} \\ $$ | ||
Commented by Tony Lin last updated on 31/Jan/20 | ||
![]() | ||
$$\left({e}^{\frac{\mathrm{1}}{{e}}} \right)^{{x}} ={x} \\ $$$${lnx}−\frac{{x}}{{e}}=\mathrm{0} \\ $$$${f}\left({x}\right)={lnx}−\frac{{x}}{{e}} \\ $$$${f}'\left({x}\right)=\frac{\mathrm{1}}{{x}}−\frac{\mathrm{1}}{{e}}=\mathrm{0} \\ $$$$\Rightarrow{x}={e} \\ $$$${f}''\left({x}\right)=−\frac{\mathrm{1}}{{x}^{\mathrm{2}} }<\mathrm{0} \\ $$$${e}\:{is}\:{the}\:{maximum}\:{value}\:\mathrm{0} \\ $$$$\therefore\left({e}^{\frac{\mathrm{1}}{{e}}} \right)^{\left({e}^{\frac{\mathrm{1}}{{e}}} \right)^{...} } ={e} \\ $$ | ||
Commented by MJS last updated on 31/Jan/20 | ||
![]() | ||
$$\mathrm{I}\:\mathrm{claim}\:\mathrm{for}\:{x}>\mathrm{0}:{y}={x}^{{x}^{{x}^{...} } } <\infty\:\Leftrightarrow\:{x}\leqslant\mathrm{e}^{\frac{\mathrm{1}}{\mathrm{e}}} \\ $$$$ \\ $$ | ||
Answered by MJS last updated on 31/Jan/20 | ||
![]() | ||
$${x}=\left(\mathrm{e}^{\frac{\pi}{\mathrm{2}}} \right)^{...} \\ $$$$\mathrm{ln}\:{x}\:=\frac{\pi}{\mathrm{2}}{x}\:\Leftrightarrow\:\frac{\pi}{\mathrm{2}}{x}−\mathrm{ln}\:{x}\:=\mathrm{0} \\ $$$${f}\left({x}\right)=\frac{\pi}{\mathrm{2}}{x}−\mathrm{ln}\:{x} \\ $$$${f}'\left({x}\right)=\mathrm{0}\:\Rightarrow\:{x}=\frac{\mathrm{2}}{\pi} \\ $$$${f}''\left(\frac{\mathrm{2}}{\pi}\right)>\mathrm{0}\:\Rightarrow\:\mathrm{absolute}\:\mathrm{minimum}\:\mathrm{at}\:\begin{pmatrix}{\frac{\mathrm{2}}{\pi}}\\{\mathrm{1}+\mathrm{ln}\:\frac{\pi}{\mathrm{2}}}\end{pmatrix} \\ $$$$\Rightarrow\:\mathrm{no}\:\mathrm{zero}\:\Rightarrow\:\mathrm{no}\:\mathrm{solution} \\ $$ | ||